(untitled) (Вісник: Міжнародні відносини, 2024)
Background. The bilateral relationship between Singapore and the United Kingdom has undergone significant transformations over the course of its history. The two countries remain important partners and continue to develop cooperation in various areas, as evidenced by the large number of bilateral documents concluded and the consistently high levels of trade and investment. In 2023, the two countries signed the Joint Declaration on the Strategic Partnership, which, according to both sides, is important for deepening relations between the two countries and expanding areas of cooperation, including collaboration in cybersecurity, financial technologies, and communications. This study aims to analyse the evolution of the format of Singapore’s engagement with the UK and identify the most priority areas of cooperation. Methods. The research methods employed in this study encompass historical, analytical, comparative, and formal-logical approaches. Elements of content analysis, economic analysis, and the method of extrapolation were applied during the study. Results. The analysis of the development of relations between the Republic of Singapore and the United Kingdom has enabled the delineation of the trajectory of partnership between the countries and the exploration of the evolution of approaches to cooperation. The historical retrospective was examined through the prism of Lee Kuan Yew’s personal interaction with the leaders of Britain at the time, as well as through a review of the gradual changes that led to the establishment of a close partnership in the trade and economic sphere. The statistical data provided and the analysis of the regulatory documents governing cooperation between the parties indicate that the financial component remains the main area of cooperation between Singapore and the United Kingdom. Conclusions. Despite changes in the global and regional geopolitical environment, the United Kingdom remains one of the most important partners for the Republic of Singapore. The common historical past has influenced the formation of similar priorities and views on global geopolitics. The two countries continue to actively interact in trade and economy and expand areas of cooperation, including cybersecurity, financial regulation, the digital economy, and information technology. For Singapore, the United Kingdom is no longer a guarantor of security in the region, but remains a reliable trade and investment partner. Instead, the United Kingdom utilises cooperation with the Republic of Singapore as an opportunity to maintain its position as a significant geopolitical player in Southeast Asia and to continue engaging with former colonies within the framework of multilateral dialogue formats with ASEAN and the Trans-Pacific Partnership.